2020
DOI: 10.1186/s13014-020-01667-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term analysis of multimodality treatment outcomes and prognosis of esthesioneuroblastomas: a single center results of 138 patients

Abstract: Background The aim of this study is to evaluate the efficacy of different treatment strategies and the potential prognostic factors of esthesioneuroblastoma (ENB). Materials and methods Between April 1984 and December 2018, 138 patients with non-metastatic ENB were retrospectively analyzed. The treatment modalities mainly included surgery alone (n = 7), radiotherapy alone (n = 33), concurrent chemoradiotherapy (n = 17), surgery combined with current chemoradiotherapy (n = 32), and surgery plus radiotherapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 24 publications
7
20
1
1
Order By: Relevance
“…The rate of regional disease at presentation in our study was 13.8%. This supports previous studies that have demonstrated rates of cervical lymph node involvement in up to 25% and that this is associated with worsening survival outcomes 27 . These findings support the addition of mKadish stage D by Morita et al 20 as both metastasis to cervical lymph nodes or distant metastasis were found to be associated with worsening OS in our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The rate of regional disease at presentation in our study was 13.8%. This supports previous studies that have demonstrated rates of cervical lymph node involvement in up to 25% and that this is associated with worsening survival outcomes 27 . These findings support the addition of mKadish stage D by Morita et al 20 as both metastasis to cervical lymph nodes or distant metastasis were found to be associated with worsening OS in our study.…”
Section: Discussionsupporting
confidence: 93%
“…This supports previous studies that have demonstrated rates of cervical lymph node involvement in up to 25% and that this is associated with worsening survival outcomes. 27 These findings support the addition of mKadish stage D by Morita et al 20 as both metastasis to cervical lymph nodes or distant metastasis were found to be associated with worsening OS in our study. However, a study utilizing the National Cancer Database has demonstrated that patients who have mKadish stage D with cervical lymph node involvement have different survival outcomes than those with distant metastasis; therefore, they propose a revision to the Kadish staging system that would separate these two types of metastases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Secondly, it gives computer tomography, MRI, or FDG-PET/CT the lead over ultrasound in the imaging of the neck. Considering the fact that an N+ situation changes the stage to Kadish-Morita D [26], worsens the prognosis [12,35], and definitively justifies adjuvant irradiation in the initial phase [42], it cannot be emphasized enough that a thorough initial scan of the patient is of major importance. A reasonable treatment algorithm should be based on thorough knowledge of the biologic (metastatic) behavior of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Para el manejo de esta enfermedad se han empleado múltiples estrategias, desde cirugía exclusiva, asociaciones de radioterapia y quimioterapia, cirugía y radioterapia hasta la asociación de las tres armas terapéuticas: cirugía, radioterapia y quimioterapia [9][10][11][12][13][14] .…”
Section: Discussionunclassified